Effect of Bradyrhizobium japonicum Strains and Inorganic Nitrogen Fertilizer on the Growth and Yield of Bambara Groundnut (Vigna subterranea (L.) Verdc) Accessions - Bitire, Tope Daniel; Abberton, Michael; Oyatomi, Olaniyi; Babalola, Olubukola Oluranti (Frontiers in Sustainable Food Systems, 2022)
Field studies were conducted in two different geographical locations: Ibadan (Ib) and Ikenne (Ik) in Nigeria (Nig), between August and December, 2019 and 2020 season. Each seed of ten accessions of Bambara groundnut (B. groundnut) used in the study, namely: TVSu-378, TVSu-506, TVSu-787, TVSu-1606, TVSu-1698, TVSu-1739, TVSu-710, TVSu-365, TVSu-475, and TVSu-305 were coated with each of the four Bradyrhizobium japonicum strains (B.japonicum) namely: FA3, USDA110, IRJ2180A and RACA6 before planting on the field in both locations and seasons, and Nitrogen fertilizer (N fertilizer (46% urea)) was applied to uninoculated seedlings at two weeks after planting (WAP), and an uninoculated control (zero inoculation and zero fertilizer application). The experiment is a 10 X 6 factorial arrangement (10 accessions of B. groundnut X 4 B.japonium strains, N fertilizer, and uninoculated control). The experiment was arranged in Randomized complete block design (RCBD) and was replicated three time with each block representing each replicate (rep). Data collected were subjected to analysis of variance and mean were separated using the (DMRT) at (P0.05) level of probability. FA3 inoculation significantly enhanced the growth traits than other inoculated strains and N fertilizer application in both locations and seasons: plant height (19.54 cm and 22.71cm), number of branches (33.63 and 62.77), number of leaves (116.54 and 209.25), terminal leaf length (5.62 cm and 6.00 cm), and width (2.09 cm and 2.56 cm) recorded at 7 WAP and 12 WAP respectively, and number of days to flowering. While the yield and yield components recorded are: pod length (13.27 cm), pod width (9.08 mm), seed length (9.39 mm), seed width (6.92 mm), weight of 100 seed (56.85 g) and yield/ha (750.72 kg) at harvest and were also significantly influenced by the inoculation of FA3 and RACA6 than other inoculated strains and N fertilizer application (46% urea) in both geographical locations and seasons.